2016 5th Brazilian Conference on Intelligent Systems (BRACIS) 2016
DOI: 10.1109/bracis.2016.071
|View full text |Cite
|
Sign up to set email alerts
|

Authorship Attribution via Network Motifs Identification

Abstract: Abstract-Concepts and methods of complex networks can be used to analyse texts at their different complexity levels. Examples of natural language processing (NLP) tasks studied via topological analysis of networks are keyword identification, automatic extractive summarization and authorship attribution. Even though a myriad of network measurements have been applied to study the authorship attribution problem, the use of motifs for text analysis has been restricted to a few works. The goal of this paper is to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Motifs also foster connectivity in real-world networks, for instance in medicine, food webs or the world wide web, carrying information forward [26][27][28][29] . Basically, each network consists of certain motif structures that might be essential for the dynamics of the whole graph.…”
Section: Motifs In a Real-world Application: The Amazon Rainforestmentioning
confidence: 99%
See 1 more Smart Citation
“…Motifs also foster connectivity in real-world networks, for instance in medicine, food webs or the world wide web, carrying information forward [26][27][28][29] . Basically, each network consists of certain motif structures that might be essential for the dynamics of the whole graph.…”
Section: Motifs In a Real-world Application: The Amazon Rainforestmentioning
confidence: 99%
“…The notion of motifs has been introduced by Milo et al 25 as the basic building blocks of complex networks. It has been shown that motifs can be identified for instance in food webs 26 , authorship attribution 27 up to transcriptional networks that control the expression of genes 28 , e.g., in tumor suppressors or E. Coli [29][30][31][32] . The so-called feed forward loop is an essential motif in such networks since it is significantly overexpressed in these real-world networks compared to typical random graphs 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Marinho et al [39] achieved an accuracy of 57.5%. In a similar study, Mehri, Darooneh and Shariati [40] identified the authorship of several Persian books written by 5 authors.…”
Section: Authorship Attribution Taskmentioning
confidence: 95%
“…ey used directed motifs with three nodes as features for document classification and compared the result with four machine learning methods. e results show that the method based on motif significantly improves the accuracy of document classification [22]. Qi et al used natural language processing technology to analyze enterprise documents, established a complex network of reserved knowledge topics, and used a fuzzy comprehensive evaluation method to calculate the 2 Complexity ability of enterprises to meet specific knowledge needs [23].…”
Section: Application Of Complex Network In Natural Languagementioning
confidence: 99%